PENGARUH PENGEMBANGAN TEKNIK MOTIVATIONAL INTERVIEWING DENGAN ASSERTIVE TRAINING TERHADAP PERILAKU ASERTIF KLIEN DI YAYASAN SEKAR MAWAR - Wahyuningtyas, Sheally; Aritonang, Nelson (Indonesian Journal of Social Work, 2024)
Abstract Assertive Training and the Motivational Interviewing Technique have been combined to form the Motivational Interviewing Assertive Technique. The principal aim of this research was to assess the impact of implementing the Motivational Interviewing Assertive (MI-a) technique on substance abuse victims exhibiting less assertive behavior, as well as to evaluate the efficacy of this intervention in promoting more assertive conduct. Assertive behavior refers to conduct that empowers an individual to freely exercise personal autonomy, defend oneself without experiencing unease, candidly and comfortably express emotions, or exercise rights without infringing upon the rights of others. The target behavior of research subjects undergoes modifications when it comes to communicating honestly, exhibiting challenges in expressing emotions, or refusing. The methodology employed in this study is single subject design (SSD). A-B-A is the research paradigm that is implemented; it consists of the following three phases: Phase A1 (baseline), Phase B (intervention), and Phase A2 (post-intervention). The behavioral observation recording sheet and the Assertive Behavior questionnaire were the instruments utilized. Among the methods of data collection are documentation studies, interviews, questionnaires, and observation. Then, it was further supported by the results of the questionnaire measurements, which indicated a substantial increase in score. Based on the results of the A1 baseline phase assessment, both subjects exhibited scores indicative of less assertive behavior. The scores for the two subjects in baseline phase A2, which occurred after the intervention, indicated that they exhibited a moderate degree of assertive behavior. The findings of this research demonstrate that the implementation of Motivational Interview Techniques and Assertive Training at the Sekar Mawar Foundation effectively enhances the assertive behavior of its clients. Keywords: Resident, Social Rehabilitation, Motivational Interview, Assertive Training